Theoretical studies of ⁶³Cu₂ + orbital Knight shifts of HgBa₂Ca₂Cu₃O₈+δ - Min-Quan Kuang; Shao-Yi Wu; Xian-Fen Hu (Физика низких температур, 2014)
The orbital Knight shifts and g factors for the tetragonal ⁶³Cu₂ + site in HgBa₂Ca₂Cu₃O₈+δ at 133 and 115 K are theoretically investigated based on the high-order perturbation formulae of these quantities for a 3d⁹ ion situated into tetragonally elongated octahedra. The theoretical results reveal good agreement with the observed values. The significant anisotropies of the Knight shifts are illustrated as the considerable local tetragonal elongation distortions of the five-coordinated Cu²⁺ sites. The results at different temperatures are also discussed in view